Integrating genomic, epidemiological and environmental modelling to uncover the dynamics of chikungunya transmission in Africa - Ramphal, Yajna (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2024.